Two natural materials found to reduce adhesion formation in a rat uterine horn model - Elçi, Erkan; Sayan, Sena; Elçi, Gülhan; Aras, İbrahim; Çim, Numan; Tolunay, Harun Egemen; Basbugan, Yıldıray (Journal of Surgery and Medicine, 2021)
Background/Aim: Post-operative pelvic adhesions cause various problems in patients, pose surgical difficulties to clinicians, and an increase in health costs. We compared the effectiveness of two natural materials, Trehalose (TRZ), Human Amnion Fluid (HAF), with oxidized regenerated cellulose (ORC) in terms of adhesion prevention after gynecological operations. Methods: In this controlled experimental study, twenty-four female Wistar Hannover rats were divided into four groups: Control, TRZ, HAF, and ORC. The control group received medication used for the surgical procedure only. 3% TRZ, cell-free HAF, and 1 cm2 ORC (interceed®) were laid on the tissue on the antimesenteric side of each uterine horn damaged with a 10-Watt bipolar cautery. Adhesions were scored 30 days after the first surgical procedure. Results: The extent, severity, degree, total adhesion, inflammation, and fibrosis scores of the control group were significantly higher than those of the TRZ and HAF groups (P<0.05 for each). There was no significant difference between the Control and ORC groups in terms of inflammation (P=0.055), but all other parameters were significantly higher in the control group compared to the ORC group (P<0.05). The TRZ group had lower total adhesion scores (P=0.019) and histopathological scores (P=0.015, P=0.001) than the ORC group. Conclusions: TRZ and HAF may be useful in preventing pelvic adhesions.